HYBRID WORK AND ITS IMPACT ON EMPLOYEE PRODUCTIVITY AND WELL-BEING IN TECHNOLOGY COMPANIES - Fitri ayu triana putri (Politeknik Siber Cerdika Internasional, 2024)
The development of digital technology has encouraged the emergence of hybrid work models as a new strategy in managing human resources, especially in the technology sector. This model combines the flexibility of remote work with the need for face-to-face interaction in the office. This study aims to analyze the impact of hybrid work on employee productivity and well-being in technology companies in Indonesia. The research method uses a quantitative approach with a survey of 120 respondents who work in digital-based technology companies. Data were analyzed using multiple linear regression to test the influence of hybrid work variables on employee productivity and well-being. The results of the study show that the implementation of hybrid work has a positive and significant effect on employee productivity through increasing time flexibility, work efficiency, and workload management. In addition, employee welfare also increases, characterized by a decrease in work stress levels, an increase in work-life balance, and the creation of better job satisfaction. This research provides the implication that hybrid work can be used as an effective human resource management strategy to face the challenges of the digital era, while supporting the achievement of company goals.